that's an odd question. One is an odd number.
yes, the product of 2 odd numbers is always an odd number. Well, the question is why. The first number is "even" + 1. Multiply both of these by your odd number. Now the "even" times "odd" is even, because every "1" in the odd number becomes a "2". And then the remaining 1 times "odd" must be odd, which is an even +1. Add it all up and you get evens everywhere except that final "1". So the result is even + 1 which is odd. There is a quicker way if you know how to multiply bracketed terms: odd x odd = (even + 1)x(even +1)= even x even +even +even +1 = must be odd.
No. The sum of 1 odd number and 1 even number must always be odd.
Odd. First subtract 1 less than your odd number, (which is obviously even) to get even - even, which is even. Then take off your spare 1 to finish up odd.
0 is a number to divide the positives and the negitives. Then it will be an even in this timeline. -2, -1, 0, 1, 2 Because it goes even odd even odd even. If zero was not there, then it would go even odd odd even.
it is a odd number it ends in 1. odd numbers end in 1 even numbers end in 2
because... odd+odd=even even+odd=odd e.g 1+1+1=3 odd+odd+odd=odd
yes, the product of 2 odd numbers is always an odd number. Well, the question is why. The first number is "even" + 1. Multiply both of these by your odd number. Now the "even" times "odd" is even, because every "1" in the odd number becomes a "2". And then the remaining 1 times "odd" must be odd, which is an even +1. Add it all up and you get evens everywhere except that final "1". So the result is even + 1 which is odd. There is a quicker way if you know how to multiply bracketed terms: odd x odd = (even + 1)x(even +1)= even x even +even +even +1 = must be odd.
No. The sum of 1 odd number and 1 even number must always be odd.
The ratio is 1:2. For every even number there are 2 odd numbers. Fibonacci Series: 0, 1, 1, 2, 3, 5, 8, 13, 21, 34, ... which is even, odd, odd, even, odd, odd, even, odd, odd, even, ... the pattern continues
Odd. First subtract 1 less than your odd number, (which is obviously even) to get even - even, which is even. Then take off your spare 1 to finish up odd.
odd
Well, the question is why. The first number is "even" + 1. Multiply both of these by your odd number. Now the "even" times "odd" is even, because every "1" in the odd number becomes a "2". And then the remaining 1 times "odd" must be odd, which is an even +1. Add it all up and you get evens everywhere except that final "1". So the result is even + 1 which is odd. There is a quicker way if you know how to multiply bracketed terms: odd x odd = (even + 1)x(even +1)= even x even +even +even +1 = must be odd. ========================== You've just read a truly impressive answer to a question slightly different from the one that was asked. The part of the question that comes after "Why if ..." is a false statement. If you multiply odd number with another number, the result is odd number ONLY if the nother number is also odd number.
0 is a number to divide the positives and the negitives. Then it will be an even in this timeline. -2, -1, 0, 1, 2 Because it goes even odd even odd even. If zero was not there, then it would go even odd odd even.
*1 is an odd number * 0 is an even number
it is a odd number it ends in 1. odd numbers end in 1 even numbers end in 2
opposite - answer will always be odd (when adding odd + even) odd + even 5 + 4 = 9 odd even + even 2 + 6 = 8 even odd + odd 3 + 1 = 4 even
The two dice can be (odd, odd), (odd, even), (even, odd), or (even, even). Thus the probability of two dice totaling an even number is 2*(1/2)*(1/2) = 1/2. 50/50